Teachers’ and Parents’ Assessments of Primary School Children’s Intellectual Investment as Predictors of Change in Need for Cognition - Anke Hufer-Thamm; Rolf Jürgens; Sebastian Bergold; Ricarda Steinmayr (Journal of Intelligence)
The present study investigated whether parents’ and teachers’ evaluations of children’s intellectual investment would predict a change in children’s need for cognition (NFC) over one year. An exploratory look at how teachers’ evaluations are predicted by a range of factors was also taken. N = 565 third-graders (298 girls; Mage = 8.40, SD = 0.59) and teachers (N = 39) were surveyed in 2021 and 2022. The parents (N = 452) provided the data in 2021. Longitudinal data were analyzed by means of latent change score models (LCSMs). Changes in the teachers’ evaluations and in the children’s cognitive engagement differed between the children. However, there was no effect of the parents’ or teachers’ assessments on the development of the children’s NFC. The change in the teachers’ assessment was negatively related to their initial judgment and the children’s age; it was positively related to the pupils’ fluid intelligence. The results and implications are discussed.